(untitled) (Research, Society and Development, 2021)
The labor market has undergone several changes over the years, resignifying the role of women and this made the understanding of productive development come to be observed by new perspectives. Thus, the objective of this work is to investigate whether there will be convergence towards gender equality in the participation of the santareno formal labor market. The database was extracted from the General Register of Employees and Unemployed (CAGED), in which information on registered admissions was used from 2004 to 2019. To achieve the objective, the Integrated Autorregressive Model of Moving Averages – ARIMA to estimate when differences in admissions between genders converge to zero. The results indicate that the level of education is an important factor for the growth of women’s participation in the formal labor market. Moreover, through the ARIMA model (0, 1, 1) it was possible to estimate, on average, the convergence of gender equality in the formal labor market, reality that should happen in November 2037, in a more pessimistic scenario, in July 2065.